2010
DOI: 10.1038/modpathol.2010.80
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-active beclin-1 correlates with favourable clinical outcome in non-Hodgkin lymphomas

Abstract: The expression of beclin-1, an oncosuppressor monoallelically deleted in 460% epithelial cancers, has been shown to be developmentally regulated in T and B lymphocytes. By interacting with either bcl-2 or class III phosphatidyl-inositol-3-phosphate kinase, beclin-1 regulates apoptosis and autophagy, two processes crucial for lymphatic tissue homeostasis. We analyzed the potential link between beclin-1-mediated autophagy and the malignant behaviour of lymphomas. The tissue expression of beclin-1 was analyzed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 40 publications
5
70
0
Order By: Relevance
“…Beclin 1 is the mammalian ortholog of the yeast Vps30/Apg6 gene, which is required for autophagosome formation, and is monoallelically deleted in a high percentage of human carcinomas (28)(29)(30). Previous studies have revealed that the promotion of the expression of Beclin 1 through reduced autophagy demonstrates anticancer effects (25,26,31).…”
Section: Discussionmentioning
confidence: 99%
“…Beclin 1 is the mammalian ortholog of the yeast Vps30/Apg6 gene, which is required for autophagosome formation, and is monoallelically deleted in a high percentage of human carcinomas (28)(29)(30). Previous studies have revealed that the promotion of the expression of Beclin 1 through reduced autophagy demonstrates anticancer effects (25,26,31).…”
Section: Discussionmentioning
confidence: 99%
“…139 When dealing with animal tissues, western blotting of LC3 should be performed on frozen biopsy samples homogenized in the presence of general protease inhibitors (Isidoro C, personal communication; see also Human). 140 Caveats regarding detection of LC3 by western blotting have been covered in a review. 25 For example, PVDF membranes may result in a stronger LC3-II retention than nitrocellulose membranes, possibly due to a higher affinity for hydrophobic proteins ( Fig.…”
mentioning
confidence: 99%
“…126 It is also possible to use anti-LC3/Atg8 antibodies for immunocytochemistry or immunohistochemistry, 140,[204][205][206][207][208][209] procedures that have the advantages of detecting the endogenous protein, obviating the need for transfection and or the generation of a transgenic organism, as well as avoiding potential artifacts resulting from overexpression (for example, high levels of overexpressed GFP-LC3 can result in its nuclear localization, although the protein can still relocate to the cytosol upon starvation), but we note that it is not always possible to detect endogenous Atg8/LC3. The use of imaging cytometry allows rapid and quantitative measures of the number of LC3 puncta and their relative number in individual or mixed cell types, using computerized assessment, enumeration, and data display (e.g., see refs.…”
mentioning
confidence: 99%
“…21 Since BECN1 positivity is a hallmark of HBV-mediated autophagy, 8 we examined BECN1 in clinical liver tissues as previously described. 22,23 As shown in Fig. 6B, diffuse staining for BECN1 was observed in the cytoplasm of hepatocytes in healthy control tissues (regarded as negative), whereas large dark brown puncta were observed (regarded as positive) in those of CHB patients.…”
Section: Hbx Facilitates the Recruitment Of Tnfrsf10b To The Autophagmentioning
confidence: 99%
“…For analysis of BECN1 positivity, the levels of BECN1 macro-aggregates were assessed as described previously. 22 Representative areas were selected from scanned IHC images and cells were identified by hematoxylin staining of the nuclei. The percentage of cells with BECN1 macro-aggregates in the selected areas was determined.…”
Section: Immunohistochemical Analysis Of Liver Tissuesmentioning
confidence: 99%